Pemenuhan Gizi Seimbang untuk Bayi dan Balita di Ranting Aisyiah Prenggan, Kota Gede, Yogyakarta - Hanifah Rahmi Fajrin; Erika Loniza (Abdimas Universal, 2022)
The toddler healthy kitchen program is an empowerment movement that emerged during the covid 19 pandemic as a solution for monitoring and fulfilling toddler nutrition through posyandu in the Aisyiah Prenggan, Kota Gede, Yogyakarta. This program involves posyandu cadres in the aisyiah community. Due to limited knowledge, funds, and the number of cadres, this activity cannot run optimally. Therefore, it is necessary to create an empowerment program to maximize healthy kitchen activities for toddlers, such as: providing healthy menus with balanced nutrition for infants and toddlers in the Aisyiah branch, Prenggan, Kota Gede. The methods that is excecuted are: doing observation to the community service location, distributing of the food menu, and checking the infants/toddlers’s weight. Community service activities have been carried out by implementing the health protocol by providing healthy menus for 20 infants/toddlers. It can be conclude that there is an increas in the infants/toddlers’s weight about 78.95%.